A castanha-da-Amazônia (Bertholletia excelsa Bompl) no contexto dos novos padrões internacionais de qualidade e segurança dos alimentos - Sousa, Walter Paixão de (2018)
Under the title "Brazilian nut (Bertholletia excelsa bompl) in the context of the new international standards of food quality and safety", in this thesis was defined as general objectives: to verify what would be required for the forest extractive products of the Amazonia, such as Brazil nuts, if they maintained or even expanded their participation in agrifood markets globalized and controlled by large transnational companies; and specifically: i) To make an evolutionary analysis of the extractive economy of renewable natural resources in the Pan- Amazon; ii) Identify the main players in governance of globalized agrifood systems and their influence on world trade; iii) To make a comparative analysis of the structural changes between two agroindustrial systems of processing and commercialization of nuts in the Pan Amazon: Bolivia and Brazil; iv) To identify and make a comparative analysis of the agroindustrial systems of processing and commercialization of Brazil nuts in the Brazilian Amazon; v) Prospecting the possibilities the adoption of innovations to the neoextrativismo of the chestnut in the Brazilian Amazon; and vi) Evaluate the possibilities of neoextrativism of forest products from the Brazilian Amazon under the perspective of ecosystem services. In order to do so, we chose as theoretical references: a) The systems and economies of the New Institutional Economy (NEI), and b) The CGV and the new standards that have been used in the governance of the interstate system by transnational corporations. And, as methodological procedures, first to fit the research as exploratory and qualitative, regardless of the quantitative approach. The main conclusions reached in this thesis were: 1. The neo / post extractivism approach would be better adapted to the development strategies of the countries of the Southern Hemisphere; 2. The standards that have become quality players in the context of globalized agri-food systems; 3. Thus, Bolivia, not Brazil, took the position of the world's largest exporter of peeled nuts; 4. This fact per se caused changes in the main production chains of Brazil nuts in the Brazilian Amazon; 5) In the context of the political approach of territories of citizenship, local S & T and ATER organizations, need a new learning, to the challenge of building a territorial platform to the neoextrativismo of the chestnut in the region; and 6. The SE approach would be understood as a global geopolitical guideline for the application of the territorial scale of natural resource management, and the responses of local environmental organizations to the management of the SEs would fall into the mosaic, a territorial negotiation instrument that , on the part of the indigenous communities, still constitutes of controversial, although remaining disposition of the actors for consensualidadas solutions.